Irving Layton and his Brother Jesus - Sherman, Kenneth (Literature and theology, 2010)
Throughout his 40-year writing career, the Canadian Jewish poet, Irving Layton, wrote often on his encounters with Christianity. This essay looks closely at four of Layton’s poems taken from different stages in his poetic development. What emerges is a sensitive appraisal of Christianity by a passionate and intelligent outsider, whose ambivalent feelings toward the dominant religion fuelled some of his most powerful poems. Special attention is paid to Layton’s critique of Christianity’s role in the Holocaust and to his attempt to refigure Jesus. It was Layton’s goal to have Jews accept Jesus as a Jewish prophet and to see the Nazarene’s teachings as continuing the Judaic revelation that began with Moses; Layton also wished to have Christians see Jesus as a Jew and to thereby accept their Semitic roots. Most importantly, in Jesus, Layton found a poetic vehicle to convey his own alienation and rebelliousness.